Evaluation of the Condition and Prediction of the Remaining Life of the Old Kutai Bridge Using the Bridge Management System (BMS) - Prabowo, Sigit Herananda; Tukimun; Admaja, Wahyu Mahendra Trias (ARRUS Journal of Engineering and Technology, 2025)
The Kutai Lama Bridge, which has been in operation for 15 years in Kutai Kartanegara Regency, East Kalimantan Province, is a critical infrastructure experiencing deterioration, with signs of damage in the expansion joints and corrosion on the steel structure. Evaluation using the Bridge Management System (BMS) indicates that the bridge is in severely damaged condition, with a Condition Index (NK) of 3. The remaining life of this bridge is 8.722 years. Based on these findings, this study recommends a rehabilitation program to ensure the bridge’s operational sustainability, with an estimated budget of IDR 7,879,754,000.00.